Visualizing Metal Content and Intracellular Distribution in Primary Hippocampal Neurons with Synchrotron X-Ray Fluorescence. - Robert A Colvin; Qiaoling Jin; Barry Lai; Lech Kiedrowski (PLoS ONE, 2016)
Increasing evidence suggests that metal dyshomeostasis plays an important role in human neurodegenerative diseases. Although distinctive metal distributions are described for mature hippocampus and cortex, much less is known about metal levels and intracellular distribution in individual hippocampal neuronal somata. To solve this problem, we conducted quantitative metal analyses utilizing synchrotron radiation X-Ray fluorescence on frozen hydrated primary cultured neurons derived from rat embryonic cortex (CTX) and two regions of the hippocampus: dentate gyrus (DG) and CA1. Comparing average metal contents showed that the most abundant metals were calcium, iron, and zinc, whereas metals such as copper and manganese were less than 10% of zinc. Average metal contents were generally similar when compared across neurons cultured from CTX, DG, and CA1, except for manganese that was larger in CA1. However, each metal showed a characteristic spatial distribution in individual neuronal somata. Zinc was uniformly distributed throughout the cytosol, with no evidence for the existence of previously identified zinc-enriched organelles, zincosomes. Calcium showed a peri-nuclear distribution consistent with accumulation in endoplasmic reticulum and/or mitochondria. Iron showed 2-3 distinct highly concentrated puncta only in peri-nuclear locations. Notwithstanding the small sample size, these analyses demonstrate that primary cultured neurons show characteristic metal signatures. The iron puncta probably represent iron-accumulating organelles, siderosomes. Thus, the metal distributions observed in mature brain structures are likely the result of both intrinsic neuronal factors that control cellular metal content and extrinsic factors related to the synaptic organization, function, and contacts formed and maintained in each region.